2009
DOI: 10.1891/0889-8391.23.3.258
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mindfulness-Based Stress Reduction on Perceived Stress: Preliminary Evidence for the Moderating Role of Attachment Style

Abstract: The current research investigated whether adult attachment style moderated the effect of mindfulness-based stress reduction (MBSR) participation on levels of perceived stress. Study completing participants (secure group n = 65; insecure group n = 66) completed pre-and postintervention self-report assessments of perceived stress. The insecure group reported significantly higher stress levels prior to MBSR participation, but both groups showed significant pre-post intervention declines in perceived stress. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 56 publications
(55 reference statements)
4
35
0
Order By: Relevance
“…In a previous study based on a (non-cancer) convenience sample and with stress as the primary outcome, the same pattern was observed, with higher levels of insecure attachment predicting greater stress reduction compared with secure attachment [26]. However, in this study, attachment anxiety and attachment avoidance were collapsed into insecure attachment [26], and thus the possible differential roles of the two dimensions were not explored [15].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In a previous study based on a (non-cancer) convenience sample and with stress as the primary outcome, the same pattern was observed, with higher levels of insecure attachment predicting greater stress reduction compared with secure attachment [26]. However, in this study, attachment anxiety and attachment avoidance were collapsed into insecure attachment [26], and thus the possible differential roles of the two dimensions were not explored [15].…”
Section: Discussionsupporting
confidence: 69%
“…In a previous study based on a (non-cancer) convenience sample and with stress as the primary outcome, the same pattern was observed, with higher levels of insecure attachment predicting greater stress reduction compared with secure attachment [26]. However, in this study, attachment anxiety and attachment avoidance were collapsed into insecure attachment [26], and thus the possible differential roles of the two dimensions were not explored [15]. We did not find statistically significant interaction effects for the remaining proposed psychological moderators, namely baseline psychological distress and alexithymia, suggesting that initial psychological distress levels and alexithymia do not influence the effect of MBCT on pain intensity.…”
Section: Discussionsupporting
confidence: 63%
“…This study extends a very small number of moderation studies to date, in which a common theme has emerged to suggest that certain psychological traits, including attachment style, 34 dispositional mindfulness, 18 and current depressive symptoms, 8 may help determine who is most likely to gain the greatest mental health benefits from participating in MBSR. Another recent trial on a clinical sample of patients diagnosed with an anxiety disorder found that individual differences in baseline depression symptoms, anxiety sensitivity, and diagnostic severity differentially moderated outcomes of group cognitive-behavioral therapy (CBT) versus an adapted MBSR program, such that CBT outperformed MBSR among those with no to mild depressive symptoms and very high anxiety sensitivity, whereas at follow-up adapted MBSR outperformed CBT among patients with moderate to severe depressive symptoms and among those with average anxiety sensitivity.…”
Section: Discussionmentioning
confidence: 52%
“…Perceived stress has also been found to relate to an assortment of psychosocial and physiological constructs, such as personality (Besser & Shackelford, 2007;Burgess, Irvine, & Wallymahmed, 2010;Candrian et al, 2008;Ebstrup, Eplov, Pisinger, & Jørgensen, 2011), affect (Besser & Shackelford, 2007;Cohen et al, 1993;Davidsdottir, 2007), self-efficacy (Ebstrup et al, 2011;Moeini et al, 2008;Trouillet, Gana, Lourel, & Fort, 2009), attachment (Cordon, Brown, & Gibson, 2009;Koopman et al, 2000;McCarthy, Moller, & Fouladi, 2001;Reiner, Anderson, Hall, & Hall, 2010), adjustment (Baker, 2004;Curtis, Groarke, Coughlan, & Gsel, 2004;Extremera, Durán, & Rey, 2007;Kulik & Heine-Cohen, 2011), depression (Candrian et al, 2008;Ghorbani, Krauss, Watson, & LeBreton, 2008;Holt-Lunstad, Birmingham, & Light, 2011), happiness (Brief, Burke, George, Robinson, & Webster, 1988;Chatters, 1988;Feist, Bodner, Jacobs, Miles, & Tan, 1995;Schiffrin & Nelson, 2010), health related behavior (Naquin & Gilbert, 1996;Rod, Grønbaek, Schnohr, Prescott, & Kristensen, 2009;Wichianson, Bughi, Unger, Spruijt-Metz, & Nguyen-Rodriguez, 2009), and health problems (Cohen et al, 1993;Lovell, Moss, Wetherell, 2011;Nielsen et al, 2008).…”
Section: Correlates Of Perceived Stressmentioning
confidence: 99%